Negativity in Communism: Ontology and Politics - Магун, Артемий (Социологическое обозрение, 2014)
The article addresses the notion of communism with a special angle of factuality and negativity, and not in the usual sense of a futurist utopia. After considering the main contemporary theories of communism in left-leaning political thought, the author turns to the Soviet experience of an “actually existing communism.” Apart from and against the bureaucratic state, a social reality existed organized around res nullius, that is, an unappropriated world that was not a collective property, as in the case of res publica. The alienation from things and from the state resulted not only in the sense of oppression, but in a new culture of a paradoxical “communality” (A. Zinoviev), where the “Other,” be it a thing or a person, appears rather as ground, not figure. This culture of a non-thematic gaze led to a formation of a communality as a given, and not as a utopian desideratum. I claim that this is a major difference between the current Western society and a post-Communist society. The former is more solidary and collectivist, but only consciously and deliberately so, operating from an individualist ontology, while the latter is individualist, but with an assumption of the “Other” as a pre-given fact. In this chiasmus, both “communisms” are problematic, so that an alternative model of individuation (Virno), rather than the atomization of an assumed collectivity, would be preferable.